Measuring WTO Approaches in Resolving Palm Oil and Biofuel Trade Disputes from Indonesia - Chairul Fahmi; Peter-Tobias Stoll (BESTUUR, 2024)
Indonesia is the world's leading producer of palm oil, with significant exports to European Union member states. However, the EU has recently imposed stricter limitations on palm oil imports, particularly from Indonesia, through policies such as the Renewable Energy Directive (RED) and RED II. This article examines the measures imposed by the WTO to address this trade dispute. Using a doctrinal approach, the study collects data from primary legal sources, such as laws, regulations, and court decisions, as well as secondary sources, including journals and books. The findings reveal that Indonesia's request for negotiations with the EU was rejected, prompting the WTO to establish a panel. However, the panel's decision lacks legal force until the appeal process is concluded. The situation is further complicated by the Appellate Body's inability to function due to the United States’ deliberate refusal to approve new appointments, leaving the dispute unresolved. Consequently, the WTO Dispute Settlement Body's ruling lacks legal certainty, raising the potential for a trade war between Indonesia and the EU. This research underscores the need for effective dispute resolution mechanisms within the WTO to address such critical trade issues.